Developing a System Framework for China’s Natural Resources Balance Sheet From the Perspective of Sustainable Development - Chen, Pinghua; Xu, Huiru; Chen, Shuiguang; Shang, Yuping; Zhang, Baoying; Zhao, Xin (Frontiers in Environmental Science, 2022)
Exploring and compiling a natural resource balance sheet is of great significance for improving both natural resource and environmental management and for realizing sustainable social and economic development. Based on a literature review of previous studies, in this study, we analyzed the composition, measurement methods, and methods used to acquire data of the major elements used in a natural resource balance sheet, as well as determined that the balance formula for the sheet should comprise natural resource assets, natural resource liabilities, and the benefits of natural resources. A basic report format for the natural resource balance sheet was compiled on this basis.